2019
DOI: 10.1111/hsc.12890
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of sharing, learning and caring: Peer support in a Finnish group of mothers

Abstract: Mothers' peer groups constitute a form of communal support that affords potential benefits but has received little attention in Finland. At present, only a few studies have investigated the support provided by peer groups of mothers. This article explores mothers' experiences of peer support in a Finnish peer group. First, the data gathered in 2015 comprise data from thematic interviews with 23 mothers participating in peer group activities. Second, the data include written notes gathered during participant ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
(44 reference statements)
0
9
0
2
Order By: Relevance
“…As women experience considerable changes in their physical, mental and social health following birth [ 72 ], a range of health professionals should be involved for their health support. One-on-one consultations can provide individualized feedback and home-based care for postpartum women [ 6 , 73 ], while small group delivery benefits from peer support which is important to alleviate emotional drain and encourage behavioural changes [ 74 , 75 ]. From our survey and interviews, combining the two formats in delivering an intervention may be beneficial for postpartum women.…”
Section: Discussionmentioning
confidence: 99%
“…As women experience considerable changes in their physical, mental and social health following birth [ 72 ], a range of health professionals should be involved for their health support. One-on-one consultations can provide individualized feedback and home-based care for postpartum women [ 6 , 73 ], while small group delivery benefits from peer support which is important to alleviate emotional drain and encourage behavioural changes [ 74 , 75 ]. From our survey and interviews, combining the two formats in delivering an intervention may be beneficial for postpartum women.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has highlighted different areas of similarity, such as being in a similar geographical location, culture, employment status, marital status, age, and recency of childbirth, as contributors to peer relationship building [ 23 , 27 ]. Having similar experiences, however, seems to be one important aspect for successful relationships identified by many studies (e.g., [ 23 , 37 , 40 ]). Research on similarity-attraction suggests that surface-level (e.g., age, ethnicity) and deep-level (e.g., attitude, values) have impact on quality of social relation with peers and program adherence behaviours [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…They also reported that not all peer support relationships were successful in shaping positive outcomes for the recipients of support. To date, only a few studies have investigated factors influencing the strength of relationship between mentors and mentees in peer support programs for mothers [ 23 , 40 ]. For example, Shorey and Ng [ 23 ] found that having flexibility in mode of contact (e.g., phone calls, WhatsApp), being a listening ear to mentees, and helping mentees feel like they are not alone facilitated relationship development.…”
Section: Introductionmentioning
confidence: 99%
“…It involves changes at various levels from everyday practices to social relations and identities which have widespread ramifications for one's sense of self, health and well‐being. Mothers' social integration with other mothers has a profound impact on the smooth transition to motherhood (Alstveit, Severinsson, & Karlsen, 2010; Eronen, 2020). Social integration refers to participation and involvement in social relationships such as contacts, friendships and group memberships in one's social environment (e.g., Grazia & Herrero, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…While new mothers' relations with family members remain fairly constant, there is often a shift from friends without children to those with children (Wrzus et al, 2013). These new relations are important, as they offer companionship and opportunities to share and compare experiences (Alstveit et al, 2010; Eronen, 2020). Other mothers in the same residential area can offer easily accessible company and social support including practical help, emotional support and advice for mothers whose social relations and daily lives with young children are often anchored close to home (Witten, Kearns, McCreanor, Penney, & Faalau, 2009).…”
Section: Introductionmentioning
confidence: 99%